Filming Up: Brazilian Elites Through an Ethnographic Lens - Alex Vailati; Walter Andrade (Vibrant: Virtual Brazilian Anthropology)
Abstract This article is based on the idea of filming up, contextualizing it in both visual anthropology and documentary history. We will first offer a brief analysis of audiovisual production concerning elites to reflect on how they are pictured and how this is of interest to anthropological studies. Considering the category of production infrastructure, we will then focus on the cinema scene in the city of Recife (Brazil), underlining how it enables the production of documentaries that focus on elites. Social inequalities within and outside cinema production infrastructure allow the affirmation of several directors, who implicitly contest this postcolonial order through their production focused on empowered groups. The analysis will show that movies are potential tools for creating ephemeral communities, enabling critical confrontation between separated social groups. Moreover, we will underline how these production practices potentially stress visual anthropological theory, forcing us to reconsider both the practices of visual fieldwork and the mainstream linguistic form that circulates within festivals and teaching institutions.